A new look at filter backwash hydraulics - (:unkn) unknown (IWA PUBLISHING, 2001)
A new approach to model media expansion during filter backwash is presented. The proposed approach is based on the assumption that the Ergun equation remains valid after fluidization. Mathematical formulas are derived for predicting expanded porosity for a given backwash velocity or backwash velocity for a given expanded porosity. These formulas can be easily used by the engineer. Values predicted using the proposed approach are in good agreement with experimental measurements.
Keywords: backwash hydraulics; Ergun equation; filtration; fluidization